Reoccurrence of West Nile virus lineage 1 after 2-year decline: first equine outbreak in Campania region - de Martinis, Claudio; Cardillo, Lorena; Pesce, Federica; Viscardi, Maurizio; Cozzolino, Loredana; Paradiso, Rubina; Cavallo, Stefania; De Ascentis, Matteo; Goffredo, Maria; Monaco, Federica; Savini, Giovanni; D’Orilia, Francescantonio; et al. (Frontiers in Veterinary Science, 2023)
West Nile virus (WNV) is the most widespread arbovirus worldwide, responsible for severe neurological symptoms in humans as well as in horses and birds. The main reservoir and amplifier of the virus are birds, and migratory birds seem to have a key role in the introduction and spread of WNV during their migratory routes. WNV lineage 1 (L1) has been missing in Italy for almost 10 years, only to reappear in 2020 in two dead raptor birds in southern Italy. The present study reports the first equine outbreak in the Campania region. A 7-year-old horse died because of worsening neurological signs and underwent necropsy and biomolecular analyses. WNV-L1 was detected by real-time RT-PCR in the heart, brain, gut, liver, and spleen. Next Generation Sequence and phylogenetic analysis revealed that the strain responsible for the outbreak showed a nucleotide identity of over 98% with the strain found in Accipiter gentilis 2 years earlier in the same area, belonging to the WNV-L1 Western-Mediterranean sub-cluster. These results underline that WNV-L1, after reintroduction in 2020, has probably silently circulated during a 2-year eclipse, with no positive sample revealed by both serological and biomolecular examinations in horses, birds, and mosquitoes. The climate changes that have occurred in the last decades are evolving the epidemiology of WNV, with introductions or re-introductions of the virus in areas that were previously considered low risk. Thereby, the virus may easily amplify and establish itself to reappear with sporadic evident cases in susceptible hosts after several months or even years.